1984
DOI: 10.1111/j.1540-8159.1984.tb04919.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Cardiac Pacing After Open‐heart Surgery: Acquired Heart Disease

Abstract: Retrospective review of 5,942 patients who underwent open-heart surgery for acquired heart disease revealed that 123 patients (2.1%) required permanent cardiac pacing postoperatively; 4.6% of these underwent predominantly valvular surgery and 0.6% had coronary bypass. The most important factors appeared to be: 1) preoperative evidence of a conduction disorder; 2) advanced patient age; 3) dense calcium in the aortic annulus; 4) valvular surgery and, especially, tricuspid valve surgery; and 5) poor myocardial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 1 publication
2
44
2
2
Order By: Relevance
“…[12][13][14][15] Previous studies have already evaluated perioperative risk predictors of PPI after cardiac surgery in large cohorts of patients with different diseases. [12][13][14][15][16][17][18] However, there are only scanty data on the development of irreversible AV block requiring PPI after aortic valve replacement, especially in the presence of isolated aortic regurgitation or in the case of combined aortic stenosis and regurgitation. In our series of 276 patients (39% with isolated aortic stenosis, 29% with isolated aortic regurgitation, and 32% with combined aortic stenosis and regurgitation), we found severe heart block requiring PPI only in 3.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Previous studies have already evaluated perioperative risk predictors of PPI after cardiac surgery in large cohorts of patients with different diseases. [12][13][14][15][16][17][18] However, there are only scanty data on the development of irreversible AV block requiring PPI after aortic valve replacement, especially in the presence of isolated aortic regurgitation or in the case of combined aortic stenosis and regurgitation. In our series of 276 patients (39% with isolated aortic stenosis, 29% with isolated aortic regurgitation, and 32% with combined aortic stenosis and regurgitation), we found severe heart block requiring PPI only in 3.2%.…”
Section: Discussionmentioning
confidence: 99%
“…4 9 12-15 The requirement for permanent pacemaker implantation (PPI) is more frequent after valve surgery (ranging from 3-6%) than after isolated coronary artery bypass grafting (0.8%). [13][14][15][16][17][18] The incidence of conduction disorders requiring permanent pacing in patients operated on for aortic valve replacement has been reported to be 5.7%. 16 However, perioperative risk predictors for PPI after aortic valve replacement are not well characterised.…”
mentioning
confidence: 99%
“…This would explain well the different incidences between those who Prevalence differs according to the type of surgery. In a retrospective review of 5,942 patients who underwent open-heart surgery to resolve acquired heart disease, it was observed that 2.1% of patients required PPM postoperatively; 4.6% of them underwent predominantly valve surgery, and 0.6% CABG surgery (Goldman, 1984). In a study of 10,421 patients a PPM prevalence of 0.4% to 1.1% after CABG, and 3.0 to 6.0% after valve operation was found.…”
Section: Prevalence Of Pacing After Cardiac Surgerymentioning
confidence: 99%
“…3. An operative view in a case of a left atrial tumor predominantly valvular surgery and 0.6% had coronary bypass (Goldman et al, 1984). They also showed that risk factors of postoperative pacemaker implantation appeared to be: 1) preoperative evidence of a conduction disorder; 2) advanced patient age; 3) dense calcium in the aortic annulus; 4) valvular surgery and, especially, tricuspid valve surgery; and 5) poor myocardial protection.…”
Section: Comment a Cardiac Surgery And Postoperative Conduction Distmentioning
confidence: 99%